Measuring Throughput and Latency Distributed Ledger Technology: Hyperledger - Riko Herwanto; Hari Sabita; Fajrin Armawan (APTIKOM SUMSEL, 2021)
In this paper, we report the measuring outcomes of Hyperledger, a Distributed Ledger, which is the derivation Blockchain Technology. A technique to evaluate Hyperledger in a limited infrastructure is developed. The measured infrastructure consists of 8 nodes with a load of up to 20000 transactions/second. Hyperledger constantly runs all evaluation, namely, for 20,000 transactions, the run time 74.30s, latency 73.40ms latency, and 257 tps. This initial evaluation can provide an overview for practitioners in making choices about the adoption of blockchain technology in their IT systems.